Competence Retention for Non-Routine-Situations in Digital Working Environments (Condition) : Studies Based on the Professions of Chemical Technician and Pharmaceutical Technician - Conein, Stephanie [Verfasser] (My University, 2023)
"Automation related skill decay and its consequences for the quality of professional work was widely being researched in high-risk industries, but no empirical studies concerning process-oriented industries have been conducted so far. The study CONDITION therefore investigated whether the problem of automation-induced skill decay also exists in the workplaces of the chemical and pharmaceutical production. Moreover, we wanted to find out which competences are affected, which factors influence the skill decay and what are the consequences. To answer the research questions a mixed methods approach was used. We started with a systematic literature analysis which was followed by 21 qualitative interviews and an online survey with 210 participants. We found out that the problem of automation-related skill decay also exists at the workplaces of the chemical and pharmaceutical production. The consequences are mostly economical, but in some incidents also the workers in the plant could be affected. Moreover, we identified some essential competences to master these situations successfully such as process-knowledge, knowledge of the actual plant, the skill to operate the plant by hand and an attitude of calmness and curiosity. To acquire these competences, it is necessary to experience the actual plant. This leads to the conclusion that the problem of automation-related skill decay certainly will become bigger because opportunities for young professionals to experience the actual plant get less since from the very first day they mostly work in a highly digitized and highly automated environment." (Authors' abstract, BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.3.4 Qualifikationswandel; G 1.2.4.1.4 Verarbeitendes Gewerbe; S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; 370; 600; Routinetätigkeit; Automatisierung; Digitalisierung; Einflussfaktor; Chemische Industrie; Pharmazeutische Industrie; Chemieberuf; Pharmazeutischer Beruf